Tourism and the new generations: emerging trends and social implications in Italy - Monaco, Salvatore (Journal of Tourism Futures, 2018)
PurposeThe purpose of this paper is to outline the profile of Italian tourists belonging to the new generations: Millennials or Generation Y (approximately people born in the 1980-1995 period) and post-Millennials or Generation Z (approximately people born in the 1996-2010 period).Design/methodology/approachAfter reviewing some of the more interesting research on Millennials and post-Millennials, the paper will present the results of an unpublished online empirical survey conducted on a sample of 200 Italian web users who agreed to participate. The questionnaire, administered via computer-assisted web interviewing system, consists of structured questions concerning the practices, attitudes, emerging needs and use of new technologies that characterize Millennials and post-Millennials, with a special focus on tourism.FindingsThe research will consider the differences between the two groups, as well as possible differences within each group linked to other socio-demographic variables (such as gender and area of residence).Originality/valueThe paper addresses a series of innovative questions: what are the practices of Millennials and Post-Millennials as tourists? What are the needs of these generations that the tourist industry must respond to? How do new technologies support Millennials and post-Millennials in their tourism choices? What are the main differences between Millennials and post-Millennials?